Fiscal Policy Implementation in Sub-Saharan Africa - Lledo, Victor (IMF Working Papers; Working Paper ;, 2011)
This paper investigates economic, political, and institutional constraints to fiscal policy implementation in sub-saharan Africa. We find that planned fiscal adjustments or expansions are less likely to be implemented the larger they are, the more inaccurate the growth forecasts they are based on, the more fragile the regulatory system in the country, and the weaker the institutions framing the design, approval, and execution of the budget. The findings support ongoing efforts in the region to improve the quality and timeliness of economic data; enhance forecasting capacity; adopt realistic fiscal plans; and strengthen governance, budgetary institutions, and public financial management procedures.